Using Supplementary Video in Multimedia Instruction as a Teaching Tool to Increase Efficiency of Learning and Quality of Experience - Ljubojevic, Milos; Vaskovic, Vojkan; Stankovic, Srecko; Vaskovic, Jelena (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
The main objective of this research is to investigate efficiency of use of supplementary video content in multimedia teaching. Integrating video clips in multimedia lecture presentations may increase students’ perception of important information and motivation for learning. Because of that, students can better understand and remember key points of a lecture. Those improvements represent some important learning outcomes. This research showed that segmentation of teaching materials with supplementary video clips may improve lecture organization and presentation in order to achieve effective teaching and learning. The context of the video content and the position of supplementary video clips in teaching material are important influences on factors for motivation and efficiency of learning. This research presents the effects of the use of supplementary videos with different context of content (entertainment and educational) as well as the effects of their position within the teaching material. The experimental results showed that the most efficient method of use of supplementary video is integration with educational video content in the middle of a lecture. This position of video insertion provides the best results. The context of video content influences efficiency of learning also. Entertainment video was not as efficient as educational, but it can be used to engage and motivate students for learning. The given results have been confirmed with a subjective assessment of students’ quality of experience with different methods of embedding video clips.